Katagalugan historiography historical sources, current trends, and future prospects - Gealogo, Francis A. (2003)
The paper is an attempt to make an assessment of regional studies and its role in the development of Philippine national history. Because of its proximity to the capital city of Manila, the Katagalugan has always been one region which has been studied and analyzed by historians and writers alike who were interested in reflecting national historical development in the context of local conditions and traditions. Spanish religious and bureaucratic officials came out with proto-anthropological, linguistic, and ethnographic studies of the Tagalogs since the consolidation of the colonial pueblo in the 16th century. The region was also the subject of inquiry of many traveller accounts for the entire period of Spanish colonial domination. During this period, archival documentation from various religious orders and bureaucratic offices yielded a lot of information on the Katagalugan. Studies on the Philippine Revolution and the Philippine-American War also contributed much to the understanding of Katagalugan history and society as some of the participants to these significant events were Tagalog themselves. The accounts on the Revolution and the Philippine-American War described the social, economic, political, and cultural conditions of the region, as well as highlighted and analyzed the critical role played by the Tagalogs in shaping Philippine national history. During the American and Japanese colonial administrations, sources on the Katagalugan focused primarily on the implementation of the colonial programs and policies on the region, as well as the reception of the Tagalogs and the ensuing social and political adjustments exhibited by the people of the region in the period between the two empires. Contemporary studies on Katagalugan after the war were mostly done, among others, by academic researchers and historians who focused on local provincial histories, political leaders from the region who wanted to highlight the significance of the Tagalog provinces in the development of Philippine post-war conditions, as well as sources revealing once again the formation of regional mass movements which took the Katagalugan as their base for the launching of mass campaigns. One critical area which will be evaluated in the paper is the interface between the indigenous and local traditions and the national and colonial trends in local regional studies. This becomes significant as the Katagalugan becomes central in the evaluation and the subject not only in the writing of local history but is also regarded as a critical player in the unfolding of national historical developments. The loci of the urban and the provincial, the central and the marginal, the colonial and the autonomous, the foreign and the indigenous - will all be regarded as loci of contestations and contradictions in the formulation of Katagalugan historiography. An analysis of the relationship between Katagalugan social formation, on the one hand, and the creation of Philippine national history, on the other, will be the area of assessment in analyzing the trends and directions of Katagalugan historiography. Hopefully, this will lend clarity to some issues and problems in the writing of other Philippine local, regional, and provincial histories, as well as in the writing of Philippine national history.
Includes bibliographical references (pages 13-20).